A three-dimensional nitrogen-doped graphene aerogel-activated carbon composite catalyst that enables low-cost microfluidic microbial fuel cells with superior performance. Issue 41 (30th August 2016) - Yang, Yang; Liu, Tianyu; Liao, Qiang; Ye, Dingding; Zhu, Xun; Li, Jun; Zhang, Pengqing; Peng, Yi; Chen, Shaowei; Li, Yat
Abstract : Low-cost electrodes were used in miniature microbial fuel cells to generate a remarkably high volumetric power density. Abstract : Microfluidic microbial fuel cells (μMFCs) are promising miniaturized power generators and bio-sensors, which combine the micro-fabrication process with bio-chip technology. However, a limited power output and considerable cost severely restrict their practical applications. Previous research has revealed that inadequate colonization of bacteria on bio-anodes as well as sluggish oxygen reduction reaction (ORR) kinetics are two main causes for the unsatisfactory power output. In this study, we have demonstrated a μMFC that has successfully addressed the aforementioned limitations by utilizing low-cost self-assembled reduced graphene oxide–nickel (rGO@Ni) foam and a nitrogen-doped graphene aerogel-activated carbon (AC@N-GA) as the bio-anode and air-cathode electrodes, respectively. The three-dimensional and macro-porous structure of the rGO@Ni foam provides a large surface area for bacterial colonization and hence largely increases the loading amount of bacterial cells. The AC@N-GA electrode shows excellent ORR catalytic performance due to the meso-porous structure and the presence of nitrogen functionalities that can serve as the catalytic sites. As a result, the μMFC achieves a maximum power density of 1181.4 ± 135.6 W m −3 (continuous-mode) and 690.2 ± 62.3 W m −3 (batch-mode) evaluated based on the volume of the reactor (50 μL). To our knowledge, this is the highest volumetric power density reported for air-breathing μMFCs and microfluidic glucose fuel cells with a similar configuration. Besides, the utilization of the inexpensive electrodes and membrane-free architecture could significantly decrease the fabrication cost of μMFCs.